Divergent antiarrhythmic effects of resveratrol and piceatannol in a whole-heart model of long QT syndrome. (15th September 2017) - Ellermann, Christian; Wolfes, Julian; Kochhäuser, Simon; Dechering, Dirk G.; Reinke, Florian; Wasmer, Kristina; Eckardt, Lars; Frommeyer, Gerrit
Abstract: Background: The polyphenol resveratrol and its metabolite piceatannol have beneficial health effects including antiarrhythmic properties in ischemia/reperfusion. The objective of this study was to determine potential antiarrhythmic effects in acquired long-QT-syndrome (LQTS). Methods and results: 26 rabbit hearts were isolated and Langendorff-perfused. The IKr -blocker sotalol (100 μM) was infused to mimic LQTS-2. Hearts were assigned to two groups. Sotalol significantly prolonged action potential duration (APD90 ) and QT-interval in both groups (group 1:APD90 : + 18 ms, p < 0.01;QT: + 59 ms, p < 0.01; group 2: APD90 : + 22 ms, p < 0.01; QT: + 30 ms, p < 0.01) and also significantly increased dispersion of repolarization (group 1: + 21 ms, p < 0.01; group 2: + 23 ms, p < 0.01). Thereafter, hearts were additionally perfused either with resveratrol (50 μM, group 1, n = 14) or with piceatannol (10 μM, group 2, n = 12). Administration of resveratrol significantly reduced APD90 (− 29 ms, p < 0.01), QT-interval(− 60 ms, p < 0.01) and dispersion of repolarization (− 26 ms, p < 0.01). In contrast, piceatannol did not significantly alter APD90 (± 0 ms) but shortened QT-interval (− 19 ms, p < 0.01) and increased dispersion of repolarization (+ 15 ms, p < 0.01). With sotalol, 7 of 14 bradycardic, AV-blocked hearts in group 1 and 8 of 12 in group 2 showed early afterdepolarizations (EAD) after lowering potassium concentration (p < 0.01each). Polymorphic ventricular tachycardia (PVT) occurred in 5 of 14 (p < 0.05) and 4 of 12 hearts (p = 0.09) with a total number of 42 (p < 0.05) and 44 episodes (p = 0.07), respectively. Additional infusion of resveratrol reduced EAD (2 of 14, p = 0.11) and PVT (1 of 14 hearts, p = 0.16, 3 episodes, p < 0.05). Piceatannol did not suppress EAD or TdP (EAD in 9 of 12 and TdP in 7 of 12 hearts, 50 episodes). Conclusion: Resveratrol showed beneficial antiarrhythmic properties in acquired LQTS. Underlying mechanism is a substantial decrease dispersion of repolarization leading to a suppression of triggered activity.